2019
DOI: 10.3171/2019.7.spine181139
|View full text |Cite
|
Sign up to set email alerts
|

Chiari malformation and syringomyelia

Abstract: Chiari malformation was first described over a century ago, and consists of posterior fossa anomalies that generally share the feature of cerebellar tonsillar descent through the foramen magnum. Our understanding of this disorder was initially based on autopsy studies, and has been greatly enhanced by the advent of MRI. The surgical management of Chiari anomalies has also evolved in a parallel fashion. Although the exact surgical technique varies among individual surgeons, the goals of surgery remain c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 71 publications
0
66
0
Order By: Relevance
“…[1][2][3][4][5][17][18][29][30][31] When CM occurs without a bony instability, the condition can be termed as a "pure CM" and traditionally, PFD has remained their treatment of choice. 9,[26][27][28][29][30][31][32][33][34][35][36][37] We found that nearly 31% of the patients had some bony anomaly like basilar impression, platybasia, assimilation of atlas, and C2-3 congenital fusion. However, the incidence of these anomalies did not vary significantly among the 3 treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][17][18][29][30][31] When CM occurs without a bony instability, the condition can be termed as a "pure CM" and traditionally, PFD has remained their treatment of choice. 9,[26][27][28][29][30][31][32][33][34][35][36][37] We found that nearly 31% of the patients had some bony anomaly like basilar impression, platybasia, assimilation of atlas, and C2-3 congenital fusion. However, the incidence of these anomalies did not vary significantly among the 3 treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, although a tetraventricular pattern of hydrocephalus is easy to diagnose on neuroimaging, it can be difficult to visualize the presence of a mobile obstructing membrane at the level of the foramen of Magendie. Other imaging techniques, such as cine MRI phase-contrast CSF flow studies, can be very helpful in detecting the presence of occult CSF blocks [19, 20], but have a low predictive value in cases of 4th ventricular outflow obstruction [21]. Karachi et al [21] explained that unlike the cerebral aqueduct, which is small in diameter, the 4th ventricle is larger and has 3 outlets, making it more susceptible to turbulence in flux and therefore more difficult to reliably visualize any obstruction to CSF flow using cine MRI [21].…”
Section: Discussionmentioning
confidence: 99%
“…Scoliosis in Chiari malformation type I is reported in up to 20% of the patients and in up to 60% of the patients with syringo- myelia [35]. Hypotheses on the occurrence of scoliosis in Chiari malformation type I are cerebellar tonsillar compression of the cervicomedullary junction and uneven expansion of a syrinx in the horizontal plane of the spinal cord [36,37]. Therefore, Chiari malformation type I should be included in the differential diagnosis of the underlying conditions of EOS.…”
Section: Chiari Malformation Type Imentioning
confidence: 99%